Aid effectiveness principles, Kenya's agriculture sector, and the challenge of donor compliance. Issue 4 (19th May 2017) - Borter, Daniel
ABSTRACT: Although most donors that support Kenya's agriculture sector subscribe to the Paris Declaration, this article reveals the ambivalence that exists between their actions and the Paris Declaration's provisions. Consequently, the article argues that the advent of the Paris Declaration has not helped to significantly improve the quality of aid activities, but on the contrary, has contributed to less engagement between donors and the Kenyan government. Given this state of affairs, the onus is on the Kenyan government and the country's civil society to push donors to honour their commitments.